KEBIJAKAN PEMERINTAH KABUPATENACEH JAYA DALAM PENGELOLAAN TAMBANG EMAS RAKYATDI GUNONG UJEUN - Aminah Aminah (Jurnal Public Policy, 2016)
This research aims to explain about the policy taken by the government of Aceh Jaya in the management of the people of the gold mine. The data that is required in writing is obtained through library research and field. Library research done with how to read text books, legislation, and other reading material related to this research. While field research done by interviewing informants. The results of the study showed that the policy of the government of Aceh Jaya in gold mining management people in Gunong Ujeun has not satisfied. This is because there are still many cases of illegal mining and still many communities miners do not know about: Perbup that has been set by the government. The district government of Aceh Jaya should work more maximum in preparing gold mine people to improve PAD. Keywords: Policy, The Management of Natural Resources and Mining Gold People